(untitled) (Bangladesh Journal of Nuclear Medicine, 2024)
Background: Single-photon emission computed tomography (SPECT) imaging of brain has emerged as a well-established and non-invasive technique for diagnosing dementia, specifically its primary subtype, Alzheimer’s disease (AD). Recent research suggested a potential correlation between the increased intima-media thickness of the carotid artery and the onset of AD. The primary objective of this study is to assess the association between carotid intima-media thickness (CIMT) measured by 2D ultrasound of the carotid artery and AD, detected by Brain SPECT imaging with 99m Technetium-Ethyl Cysteinate Dimer (99m Tc ECD). Patients and Methods: This cross-sectional study was conducted at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS) between March 2021 to June 2022. Ethical approval was obtained from Medical Research Ethics Committee (MREC). The study included 65 patients with suspected or confirmed dementia. Data collection included Mini Mental State Examination (MMSE) score of neurology and associated laboratory reports. All the participants underwent 2D ultrasonography of carotid artery to measure carotid intima-media thickness (CIMT) and a brain SPECT with 99mTc-ECD followed by image interpretations using the easy Z score imaging system (eZIS). Result: The mean age of the study population was 63.8 ± 9.5 years, with a male predominance (69.2%). The most prevalent comorbidities were hypertension and dyslipidemia (24.6%) and diabetes mellitus (13.8%). The majority of patients scored in the 25.27 range on the MMSE. Regarding CIMT, 40% of patients had moderate CIMT, 35.4% had normal CIMT, and 24.6% had mildly increased CIMT. Brain SPECT results indicated that 69.2% of patients had Alzheimer’s disease (AD), while 30.8% had dementia other than AD. Among AD patients, 71.1% had mild AD, 20.0% had moderate AD, and 8.9% had severe AD. An unpaired t-test revealed a slightly higher mean CIMT value in AD patients (1.28±0.58 mm vs. 1.25 ± 0.60 mm, p = 0.873), though this difference was not statistically significant. Conversely, ANOVA and Pearson’s correlation tests demonstrated a statistically significant association between CIMT and the severity of AD, as represented by the Z-score (r = +0.693, p<0.001). Conclusion: The study highlights the significance of carotid intima-media thickness (CIMT) in Alzheimer’s disease (AD) and non-AD patients, suggesting its use in initial assessment and follow-up measures. Bangladesh J. Nuclear Med. 27(1): 49-55, 2024